2017
DOI: 10.26887/ekse.v19i2.149
|View full text |Cite
|
Sign up to set email alerts
|

Katurangganing Kutut

Abstract: Karya Seni Lukis berjudul Katurangganing Kutut terinspirasi dari pengalaman memelihara burung perkutut dan legenda Falsafah Jawa tentang Katuranggan burung Perkutut. Permasalahannya dibahas melalui pendekatan; Apa yang menjadi dasar ” Katuranggan burung Perkutut “ diangkat menjadi sumber ide dan konsep penciptaankarya seni ? Bagaimana merumuskan konsep karya seni berdasarkan gagasan “ Katuranggan burung Perkutut ” dalam implementasinya, Karakteristik dan figure burung Perkutut sesuai dengan Katuranggannya, dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Burung perkutut sudah lama dikenal orang. Zaman dahulu, Burung perkutut merupakan burung peliharaan orang-orang penting, seperti raja, ningrat atau bangsawan, pejabat kerajaan, dan pemuka masyarakat [1] [2]. Sekarang ini pecinta burung perkutut merata disemua lapisan masyarakat.…”
Section: Pendahuluan 11 Latar Belakangunclassified
See 3 more Smart Citations
“…Burung perkutut sudah lama dikenal orang. Zaman dahulu, Burung perkutut merupakan burung peliharaan orang-orang penting, seperti raja, ningrat atau bangsawan, pejabat kerajaan, dan pemuka masyarakat [1] [2]. Sekarang ini pecinta burung perkutut merata disemua lapisan masyarakat.…”
Section: Pendahuluan 11 Latar Belakangunclassified
“…8 unsur kesempurnaan hidup adalah wanita, garwa, wisma, turangga, curiga, kukila, waranggana, dan pradangga. Burung perkutut pada falsafah cupu manik hasta gina sendiri dilambangkan dengan kukila [2] [7].…”
Section: Pendahuluan 11 Latar Belakangunclassified
See 2 more Smart Citations
“…It is believed that the bird's call may attract and bring good luck to the house owner. While Javanese have cultural belief that perkutut or kutut (Geopelia striata, Family of Columbidae) is considered as lucky-conveyor bird, as a result, this birds have been popularly kept as bird pet and traditionally entitled as Katurangganing kutut which is inspired from experience of nurturing kutut bird and the legend of Java philosophy on the Katurangan of this bird (Sanjaya et al 2017). Based on the ethnoornithology studies, it can be revealed that every ethnic community across culture in Indonesia, has cultural deep knowledge on birds, and birds are given various local folk names (Iskandar in prep).…”
Section: Folkloric Birdsmentioning
confidence: 99%